A dupla instância do bem integrado: análise dos critérios de restauração sob a ótica das artes e da arquiteturasobre o ornamento aplicado - Maria Angela Reis de Castro (2009)
This master thesis concerns about applied arts restoration criteria. To do so, it was done a review on different historical contexts centuries XVIII, XIX and XX with their influences in arts and architecture and on restoration criteria in order to verify the evolution of the thoughts at this field, what makes possible to compare them and identify divergences between them. At last, the study propose the necessity to identify one architectural instance for the applied arts restoration, where they can be evaluated not only as a single work of art or as a part of the building, but mainly as un integrated expression of art and architecture, where an alteration in one influences the other.